Public spending in Ghana: An assessment of national level data (1995 – 2005) - Osei, Robert Darko; Osei-Akoto, Isaac; Quarmine, William; Adiah, George Adayi-Nwoza (International Food Policy Research Institute, 2007)
Ghana’s Growth and Poverty Reduction Strategy (GPRS II; November, 2005) which spans the period 2006 – 2009 intends to shift the strategic focus of the country’s development agenda from the direct anti-poverty objectives of the GPRS I to a more growth-oriented strategy. The development agenda of the country, as set out in GPRS II is now geared towards achieving middle income status by 2015. In other words, accelerating economic growth is to be given priority. This growth acceleration is to be complemented by policies aimed at empowering the vulnerable and excluded, so that the poor can share in the benefits of growth.... This paper reviews the trends in public expenditure as well as key development outcomes over the last 10 years (1995 – 2005).